Land Cover Change Detection in Garabulli using Remote Sensing and GIS Techniques in the period of 1992 to 2010 - Abdu Salam, Moneer Imran; Elaalem, Mukhtar Mahmud; Dribika, Mustafa Shaker; Ekhmaj, Ahmed; Ezlit, Younes (Al-Mukhtar Journal of Sciences, 2016)
This study aimed to monitor the change in land cover in Garabulli regionduring the period (1992 - 2010) by using remote sensing technique. The satellite imagesused in this study were obtained from the satellite Spot 4 for each of years of 1992 and 2000 and Spot 5 for year 2010. The supervised classification was performed on the Spot images using maximum likelihood classification. The land cover changes were detected during different times by land cover maps which were produced using ENVI software. The results have revealed clear changes in the land cover whereas barren land, agricultural land, and urban area have been increased by 37.6%, 35.1%, and 28% between 1992 and 2010, respectively. Meanwhile, forest and rangeland were decreased between 1992 and 2010 by 65% and 41%, respectively. The results showed that declining of forest and rangeland may lead to rapidly increase of desertification. Additionally, the present study revealed that the remote sensing techniques can be used effectively in monitoring and interpreting the changes which may occur in the land cover.